Agent AI Towards a Holistic Intelligence - Huang, Qiuyuan; Wake, Naoki; Sarkar, Bidipta; Durante, Zane; Gong, Ran; Taori, Rohan; Noda, Yusuke; Terzopoulos, Demetri; Kuno, Noboru; Famoti, Ade; Llorens, Ashley J.; Langford, John; et al. (arXiv: 2403.00833, 2024)
Recent advancements in large foundational models have remarkably enhanced our understanding of sensory information in open-world environments. At this pivotal moment, it is crucial to the AI research trend toward excessive reductionism and returning to the AI principles inspired by the holistic philosophy of Aristotle. Specifically, we emphasize developing “Agent AI”, an embodied system that integrates large foundation models into agent actions. The emerging field of Agent AI spans a wide range of existing embodied and agent-based multimodal interactions, including robotics, gaming, and diagnostic systems. We emphasize the importance of integrating recent large foundational models to enhance intelligence and interaction capabilities. Furthermore, we discuss how agents exhibit remarkable capabilities across a variety of domains and tasks, challenging our understanding of learning and cognition. This paper we aim to broaden the research community’s perspective on achieving holistic intelligence, while highlighting the need for an integrated approach that considers the agent’s purpose, functionality, and interaction. Finally, we reflect on a deeper discussion of these Agent AI topics from a mainstream and interdisciplinary perspective. This discussion illustrates AI cognition and consciousness within the scope of scientific discourse, and may serves as a basis for future research directions and social influences.